Bioactive constituents from Vitex negundo var. heterophylla and their antioxidant and α-glucosidase inhibitory activities. (August 2017) - Hu, Ping; Li, Da-Hong; Jia, Cui-Cui; Liu, Quan; Wang, Xiao-Fei; Li, Zhan-Lin; Hua, Hui-Ming
Graphical abstract: Highlights: Systematic phytochemical investigation of Vitex negundo var. heterophylla led to the isolation of twenty-four compounds. Four compounds were new and five others were obtained from Vitex genus for the first time. Six flavonoids showed more potent DPPH radical scavenging capacity thanl -ascorbic acid. Isoorientin-6″- O -caffeate was an even more effective antioxidant and α -glucosidase inhibitor than the positive controls. Abstract: Vitex negundo L. var. heterophylla (Franch.) Rehd. is widely accepted as a functional and medicinal food in China because of the presence of bioactive components which improve the physical condition. In the present study, the bioactive constituents, antioxidant, α -glucosidase and DPP-IV inhibitory activities of V. negundo var. heterophylla were investigated. Two new coumarin glycosides, vitexnegheteroins I-J (1 –2 ), and two new iridoid glycosides, vitexnegheteroins K-L (3 –4 ), were isolated from the leaves and seeds of V. negundo var. heterophylla, together with twenty known compounds. Seven compounds presented stronger antioxidant activities thanl -ascorbic acid in both DPPH and ABTS assays. Among them, isoorientin-6″- O -caffeate (22 ) also exhibited more potent α -glucosidase inhibitory activity than acarbose with an IC50 value of 0.24 ± 0.02 μM. These findings further revealed the bioactive components of this edible aromatic plant and disclosed the potency of it to be developed as new antioxidant and α -glucosidase inhibitory agents.